Optimisation of composition and cast temperature for continuous semisolid extruded Al–Sc–Zr electrical conductor. (July 2014) - Tie, D.; Guan, R.-G.; Cui, T.; Ling, C.; Wang, X.; Guan, X.-H.
<x content-type="archive" xml:space="preserve">Abstract</x> Three aluminium alloy conductive wires, Al–0·16Sc (wt-%), Al–0·16Zr (wt-%) and Al–0·12Sc–0·04Zr (wt-%) were designed and produced by continuous rheo-extrusion process. The influences of composition and pouring temperature during cast process on the microstructure, mechanical and conductive properties of the wires were studied. Results show that compared with the other two alloys, both mechanical and conductive properties of Al–0·12Sc–0·04Zr alloy after aging treatment was significantly higher: the ultimate tensile strength is 160 MPa and the conductive rate is 66·99% IACS. The optimised pouring temperature during the cast process was 690°C, and the most favourable mechanical and conductive properties were achieved at this temperature owing to the alloy's smallest grain size.